STUDI KORELASI WPT ( WONDERLIC PERSONNEL TEST ) DAN IST ( INTELLIGENZ STRUCTUR TEST ) - Sulisworo Kusdiyati (Psympathic : Jurnal Ilmiah Psikologi, 2010)
Psychological testing in high school, university and assessment of new employee were used in order to ease stakeholder for sorting and placement purpose. These tests generally include intellectual capability, personality test and performance test. There are numerous tests that can be used for this purpose and some of them quite popular among many assessor such as IST-70 and WPT. However it is known that the intelligence score as result from IST-70 and WPT were quite different. IQ score from WPT generally resulted 1-5 point lower from IST. The question now is which is from both test that considered as a valid result? This research was conducted in purpose of gathering empirical data regarding s-factor and g-factor in IST, correlation element between WPT and IST, and last differences between both tests. Thus, this research can be considered as correlation research. The assumption used in this research are (1) correlation between subtest in IST, (2) subtest in IST with WPT;(3) IQ score result with WPT and IST; and (4) differences between of IQ score resulted by WPT and IST. It was then concluded that IST measure s-factor and g-factor while WPT only measure g-factor.